Exploring the negative criticism of readers' comments on online news on the construction of a new capital city of Indonesia (IKN) - Dadang Suganda; Susi Yuliawati; Ani Rachmat; Tatang Suparman (Cogent Arts & Humanities)
The present research investigated comments on political reports that elicited negative criticism, predominantly influenced by the readers' heated political perspectives. The study utilised lexical and pragmatic analyses to explore a corpus of 1000 reader comments on Indonesian news items concerning a new capital city construction, Ibu Kota Nusantara (IKN). We analysed the language manifestation of negative criticism through word frequency, the speech acts that underpin it, and the stance-taking position of the commenters. The results indicate that the most common words in the negative criticism include nouns, pronouns, and negation lexis. Commenters employed such words to amplify the effect of their negative criticism. The speech acts underlying the negative criticism include evaluative, directive, analytical, and a combination of two to three speech acts, with evaluative being the most prominent. The commenters serving as judges represent the most prominent role due to the direct correlation between the speech act and the stance-taking function. Divergent political viewpoints are a significant factor in the construction of IKN, which has received negative criticism from commenters. In addition to spotlighting on negative criticism, this paper can serve as a representative case of how a study integrating corpus linguistics and pragmatics can be applied to other languages or social interactions in digital media.